Social variation in adults’ lexical availability in Las Palmas de Gran Canaria: quantitative analysis and comparative notes - Medina Peñate, Inmaculada (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This work is a sociolinguistic study of the lexical availability of Las Palmas de Gran Canaria, based on a sampleof 72 informants and obtained according to the criteria of the PRESEEA project. After detailing quantitative aspects suchas word average, number of different words, cohesion index or productivity of centers of interest, the incidence of socialvariables (‘sex’, ‘age’, ‘level of education’ and ‘socio-economic level’) on the lexical availability of adult native speakersof Las Palmas de Gran Canaria is analysed. Thus, it is found that the factor ‘sex’ has less influence on the results, but ageallows us to observe the progressive increase in lexical ability, which stabilises in adulthood and decreases in the thirdgeneration, always in correlation with the level of education. The level of education and socio-economic status werefound to be the factors that had the greatest impact on the results, with a statistically significant positive correlationbetween the years of study and the number of words of each informant.
Keywords: lexical availability; PRESEEA; Canarian Spanish; sociolinguistics